ERKEK İNFERTİLİTESİNDE HİPERPROLAKTİNEMİNİN SEMEN PARAMETRELERİ ÜZERİNE ETKİSİ - ALICI, Bülent; ÇİTÇİ, Arman and ÖZKARA, Hamdi and AKKUŞ, Emre and HATTAT, Halim (Cerrahpaşa Medical Journal, 2019)
Background and Design. The effect of prolactin (PRL) on spermatogenesis and semen parameters is not known well. To determine the relation between hyperprolactinemia and spermatogenesis we evaluated 85 infertile patients with hyperprolactinemia. We anaiysed the serum PRL, folliclestimulating hormone, luteinizing hormone, total testosterone levels and obtained at least two semen anaiyses in all cases. Results. In patients using bromocryptine mesylate for hyperprolactinemia, serum PRL levels returned to normal levels within 4 months, but semen analyse parameters did not differ from baseline values. Conclusion. Hyperprolactinemia has a small effect on sperm density, motility and morphology. Bromocryptine mesylate offers no additive therapeutic effect for the hyperprolactinemia in male infertility.